Exploring the Reasons for Dropouts of Injectable Contraceptive in Burdwan Municipal area, West Bengal, India: Beneficiaries’ and Service Providers’ Perspectives - Arif Hossain; Pramit Goswami; Kaushik Mitra; Pranita Taraphdar; Suman Sannigrahi; Soumik Dandapat (Current Medical Issues)
Introduction: The inclusion of the Injectable Contraceptive, Antara Programme into family planning services signals a shift in the nation’s perspective and helps recipients achieve their goals for reproductive health. Depot medroxyprogesterone acetate (DMPA), marketed as Antara injection is considered a highly effective, long-acting reversible contraceptive, but it has limited acceptability. Hence the study was done to explore the reasons for dropouts of injection Antara from the perspective of beneficiaries and service providers in Antara clinics of Burdwan Municipal area of Purba-Bardhaman district, West-Bengal. Methodology: A descriptive type of qualitative research was conducted from February to July 2023 through in-depth interviews (IDIs) of 40 beneficiaries and focus group discussion (FGD) among 10 ANMs-Auxiliary Nurse Midwives. Data collection was done by audio recording of each IDI, FGD, and as well as by taking notes after achieving consent. Finally, inductive thematic analysis was carried out. Results: The reasons for dropouts of Antara injections among beneficiaries were found to be side effects (irregular bleeding, abdominal pain), lack of awareness, and familial barriers. Additionally, the significant challenge of recalling and visiting the clinic again for repeated injections was also recognized as a hindrance to sustained usage. Service providers cited stockouts, procurement issues, and lack of training and counseling as reasons for discontinuation. Both beneficiaries and service providers cited sociocultural factors, and lack of knowledge as a barrier to consistent use of Antara injections. Conclusions: The current study has shed some insight into the factors for the dropouts of Antara as a method of family planning. The study’s findings are anticipated to be applied in formulating regulations that will increase compliance with Antara and make the program more acceptable and consumer-friendly.